NASF Leads Chromium Symposium for California Air Resources Board (Products Finishing, 2021)
The National Association for Surface Finishing (NASF) and its California chapters held a chromium plating symposium for the California Air Resources Board (CARB) on Wednesday, Mar 3. As part of CARB's consideration on possible regulatory options to address hexavalent chromium, state officials agreed to NASF's suggestion to convene a slate of industry experts to discuss the status of trivalent chromium plating technology and the current barriers and timelines for a broad application of trivalent chromium processes. The symposium highlighted the surface finishing industry's proactive approach to promoting innovative technologies and implementing risk management options for hexavalent chromium and included subject matter expert panels in four areas: decorative chromium plating; functional or hard chromium plating; implications for aerospace and defense applications; and perspectives from job shops in California.